Association of a 7‐year percent change in fat mass and muscle mass with subsequent cognitive dysfunction: the EPIDOS‐Toulouse cohort. Issue 3 (26th July 2013) - Abellan van Kan, Gabor; Cesari, Matteo; Gillette-Guyonnet, Sophie; Dupuy, Charlotte; Vellas, Bruno; Rolland, Yves
Abstract : Background: Cognitive dysfunction and changes in body composition share common pathophysiological pathways. The aim of the present paper was to evaluate whether changes in appendicular muscle mass (AMM) and fat mass (FM) are associated factors with an increased risk of cognitive dysfunction in community‐dwelling older women. Methods: A nested case–control study was performed in 181 women aged 75 years and older from a subsample of the Epidemiologie de l'Osteoporose participants from Toulouse. Body composition parameters at inclusion and 7 years later (assessed by dual energy X‐ray absorptiometry), and the presence of cognitive dysfunction (dementia and mild cognitive impairment) at 7 years of follow‐up, assured by two memory experts based on best clinical practice and validated criteria, were obtained. Multivariate logistic regression models assessed the association of percent change in AMM and FM with risk of cognitive dysfunction. Results: At 7 years of follow‐up, 15 participants suffered from dementia, 6 suffered from mild cognitive impairment, and 160 were cognitively normal. Neither body composition changes nor gait speed was found to be statistically associated with cognitive dysfunction after controlling for potential confounders. Only age, over 85 years, was associated with an increased risk of subsequent cognitive impairment (odds ratio 3.10; 95 % confidence interval 1.07–8.87). Conclusions: No significant association could be evidenced between changes in body composition and cognitive dysfunction. Due to the small sample size, statistical power could be an issue. The study could also suggest the possibility that the risk of cognitive dysfunction is not mediated by changes in body composition.